2018
DOI: 10.1108/ijppm-11-2016-0257
|View full text |Cite
|
Sign up to set email alerts
|

Best supply chain management practices and high-performance firms

Abstract: Editor's Comments We are extremely thankful to the Editor's comments for the useful suggestions. We have taken all your observations and recommendations on board and made the necessary modifications and improvements, when necessary, in the revised version of our paper. We sincerely hope that our revised version satisfies your queries/concerns. We have used the track changes function to show the changes we have made in the revised paper We have also provided point wise answers to the raised queries below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 68 publications
5
42
0
Order By: Relevance
“…[30,72,87,101] Findings show that most of the identified metrics are economic, which is coherent with the prominent attention that this dimension has received in the literature over time. Both recent and older publications that address the effects of SCM on performance, without explicit consideration of a holistic sustainability approach, have defined performance through a competitive advantage [7], operational [5] market, and financial constructs [108].…”
Section: Financialmentioning
confidence: 99%
“…[30,72,87,101] Findings show that most of the identified metrics are economic, which is coherent with the prominent attention that this dimension has received in the literature over time. Both recent and older publications that address the effects of SCM on performance, without explicit consideration of a holistic sustainability approach, have defined performance through a competitive advantage [7], operational [5] market, and financial constructs [108].…”
Section: Financialmentioning
confidence: 99%
“…Studies by Walden [18] have found that employers have undergone various changes in recent times including the use of innovative ways of doing business. This has been brought about by the requirement of organizations (employers) to be highly competitive due to internal and external pressures brought about by globalization and other factors such as the COVID-19 crisis [3]. As a result, the output (graduated students) needs to have competences and knowledge that can enable them to work more efficiently to maximize output and production [20].…”
Section: Finding 2: Supply Chain Management Models Strengthen the Quality Of Higher Learning Offered By Institutionsmentioning
confidence: 99%
“…Within the gulf region, there are many local higher education institutions while others are established in collaboration with international universities [2]. Within this region, Institutions of higher education are increasingly required to improve the quality of outcomes, tackle competition from international universities, adapt to the rise in globalization as well as address the intricacies of their operations [3]. The other key pressure faced by higher education (thereafter referred to as HE) institutions is the current COVID-19 crisis which limits the level of face-to-face interaction allowed between learners and the faculty staff in order to contain the epidemic [4].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, the impact of SCI on profitability (Kim, 2006;Chen et al, 2007;AL-Shboul et al, 2018;Amoako et al, 2020) is most investigated in previous studies. Notably, companies are profit-seeking.…”
Section: Financial Performancementioning
confidence: 99%